Detection of DNA Nucleotides on Pretreated Boron Doped Diamond Electrodes - Garbellini, Gustavo S. [UNESP]; Uliana, Carolina V. [UNESP]; Yamanaka, Hideko [UNESP] (Soc Brasileira Quimica, 2011)
The individual detection and equimolar mixture of DNA nucleotides guanosine monophosphate (GMP), adenosine monophosphate (AMP), thymidine (TMP) and cytidine (CMP) 5'-monophosphate using square wave voltammetry was performed on boron doped diamond (BDD) electrodes cathodically (Red-DDB) and anodically (Oxi-DDB) pretreated. The oxidation of individual DNA nucleotides was more sensitive on Oxi-BDD electrode. In a simultaneous detection of nucleotides, the responses of GMP, AMP, TMP and CMP were very adequate on both treated electrodes. Particularly, more sensitive and separate peaks for TMP and CMP on Oxi-BDD and Red-BDD electrodes, respectively, were observed after deconvolution procedure. The detection of nucleotides in aqueous solutions will certainly contribute for genotoxic evaluation of substances and hybridization reactions by immobilizing ss or ds-DNA on BDD surface.
Keywords: DNA; nucleotides; diamond electrodes; surface termination